The stage and social struggle in early modern England - Howard, Jean E. (Jean Elizabeth), 1948- (Routledge, 1994)
A ground-breaking study of the social and cultural functions of the early modern theatre. Jean Howard looks at the effects of drama and the stage on early modern culture in an exciting and eminently readable work.